Analysis of The Gross Motor Skills of Children Aged 5-6 Years in Football Games at TK Negeri Pembina Sibolangit - Barus, Aldi Pranata; Aman Simaremare (MultiTech Publisher, 2023)
This research was conducted with the aim of describing the gross motor skills of children aged 5-6 years in the aspects of: 1) Strength, 2) Agility, 3) Balance through playing football. The type of research used is descriptive qualitative. The subjects in this study were 10 children aged 5-6 years at TK Negeri Pembina Sibolangit. The results showed that: 1) the gross motor skills of children in the strength aspect showed that 70% had developed as expected and 30% had not developed as expected. 2) children's motor skills in the agility aspect show that 60% of children develop as expected and 40% have not developed as expected. 3) gross motor skills of children in the aspect of balance, 80% of children's abilities have developed as expected and 20% have not developed as expected.